The Effect of Independent Cash Tim (ATM) Revenue On Sharia Banking Performance in Indonesia (2016-2020) - Arif, Muhammad; Habibie, Ahmad Musabiq (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
In 2020, around 50.3% of Indonesian people frequently use ATM services for transactions. The impact of ATM on banking performance has been the subject of various studies in the field of electronic banking with mixed results. Therefore, further investigation is needed to obtain empirical evidence regarding the effect of ATM income on bank performance. This study aims to examine the impact of ATM revenue on the performance of Islamic banking in Indonesia for the 2016-2020 period.A descriptive statistical method was used, utilizing secondary data from a time series consisting of 30 samples. The analysis used in this study is multiple regression which includes descriptive analysis test, normality test, linearity test, simple linear regression analysis, determinant coefficient test (R2), correlation coefficient test, and hypothesis testing (t-test).By using SPSS Software Version 25, the results showed a significance value (sig.) of 0.033 for the ATM variable (X). As Sig. 0.033 0.05 indicates profitability, the hypothesis is accepted. This means that there is an influence of ATM (X) on the performance of Islamic banking (Y). The coefficient of determination (R2) yields a value of 0.152 which means the influence of the ATM variable (X) is 15.2% on the performance of Islamic banking (Y). The remaining 84.8% is associated with variables not examined in this study.Keywords: Independent, Shariah Banking, Performance.